2016
DOI: 10.1007/s13595-016-0585-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-thinning in four pine species: an evaluation of potential climate impacts

Abstract: Key message Self-thinning lines are species- and climate-specific, and they should be used when assessing the capacity of different forest stands to increase biomass/carbon storage. Context The capacity of forests to store carbon can help to mitigate the effects of atmospheric CO2 rise and climate change. The self-thinning relationship (average size measure ∼ stand density) has been used to identify the potential capacity of biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
1
19
0
7
Order By: Relevance
“…Reported mean values of density after the fire, for maritime pine, are scarce and the ones being circulated, quite variable (due, in part, to a plot-size dependency as noticed by Freitas [7]), bringing additional inaccuracy to the expected density values at a given age. For example, three years after the occurrence of fires, Rodrigues [8] and Alegria et al [9], respectively, report densities of 42.5 seedlings of maritime pine per 25 m 2 and 960 plants per 500 m 2 (17,(0)(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)190 plants per ha, respectively), while Calvo et al [10] refer to average values of 6.53-11.53 seedlings per m 2 (65,300-115,300 plants per hectare). Secondly, there is a gap of knowledge about the attainable maximum densities at a given size for young stands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported mean values of density after the fire, for maritime pine, are scarce and the ones being circulated, quite variable (due, in part, to a plot-size dependency as noticed by Freitas [7]), bringing additional inaccuracy to the expected density values at a given age. For example, three years after the occurrence of fires, Rodrigues [8] and Alegria et al [9], respectively, report densities of 42.5 seedlings of maritime pine per 25 m 2 and 960 plants per 500 m 2 (17,(0)(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)190 plants per ha, respectively), while Calvo et al [10] refer to average values of 6.53-11.53 seedlings per m 2 (65,300-115,300 plants per hectare). Secondly, there is a gap of knowledge about the attainable maximum densities at a given size for young stands.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that shade tolerant species tend to show a lower slope [15] and a higher intercept [18], due to the variation in self-tolerance. Some of the references [19][20][21][22] indicate that the change of the trajectory and/or the maximum value of density depends on the location of the stands, as well as on the climate characteristics. Deviance from the straight line is also recurrently mentioned [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…A single self-thinning line has routinely been used to describe all conditions at a regional scale (Reyes-Hernandez et al 2013;Toïgo et al 2015). However, the boundary lines varied among sites (or regions) for a given species (Brunet-Navarro et al 2016;Charru et al 2012). In this study, we fitted self-thinning models that explain this variability at different sites to provide self-thinning trajectories accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these results, we found that steeper slopes for Chinese fir occurred in wet areas (Table 3). In other regions, aridity was the primary explanation of limiting tree growth in tropical and lowland Mediterranean regions (Segura et al 2003;Banin et al 2012;Brunet-Navarro et al 2016). Water stress may alter the size symmetry of competition, as well as the level of stress (Chu et al 2010).…”
Section: Effects Of Climate On Self-thinning Linementioning
confidence: 99%
See 1 more Smart Citation